Chemical Resistance of Thermoplastics - Woishnis, William, 1958-; Ebnesajjad, Sina (Waltham, MA ; Oxford : William Andrew, 2012)
"Chemical Resistance of Thermoplastics is a unique reference work, providing a comprehensive cross-referenced compilation of chemical resistance data that explains the effect of thousands of exposure media on the properties and characteristics of commodity thermoplastics. The two volumes cover thermoplastics grouped within the following parts: - Acrylic Polymers and Copolymers - Acrylonitrile Polymers - Cellulosics Polymers - Ionomers - Olefinic Polymers - Polyacetals - Polyacetals - Polyamides - Polycarbonates - Polyesters - Polyurethanes - Polycarbonates - Styrene Copolymers - Styrene Copolymers - Vinyl Chloride Polymers - Vinyl Polymers. The single most comprehensive data source covering the chemical resistance properties of high consumption volume commercial thermoplastics A rating number is provided for each test, summarizing the effect of the exposure medium on the given thermoplastic The data covered in the two volumes is also provided as an online publication offering extended navigation and search features."--Publisher's description.
VOLUME 2 -- Part 6. Polyacetals -- 12. Acetal, Homopolymer (POM Homopolymer) -- Part 7. Polyamides -- 14. Nylon 12 (PA 12) -- 15. Nylon 46 (PA 46) -- 16. Nylon 6 (PA 6) -- 17. Nylon 610 (PA 610) -- 18. Nylon 612 (PA 612) -- 19. Nylon 66 (PA 66) -- 20. Nylon, amorphous (PA, amorphous) -- 21. PoIycaprolactones -- 22. Polyamide, Nylon -- 23. Other Polyamides -- Part 8. Polycarbonates -- 24. PoIycarbonates -- Part 9. Polyesters -- 25. Polyester, PET -- 26. Other PoIyesters -- Part 10. Polyurethanes -- 27. Polyurethanes -- Part 11. Styrene Copolymers -- 28. ABS -- 29. Styrene Acrylonitrile (SAN) and Other Copolymers -- Part 12. Styrene Polymers -- 30. Polystyrenes (PS) -- 31. Polystyrene, Impact -- Part 13. Vinyl Chloride Polymers -- 32. Polyvinyl Chlorides (PVC) -- Part 14. Vinyl Polymers -- 33. Vinyl Polymers -- Alphabetical List of Exposure Media -- CAS Registry Numbers--Chemical Sort -- CAS Registry Numbers--Numeric Sort.
Includes bibliographical references.
Keywords: Thermoplastics -- Chemical resistance -- Handbooks, manuals, etc; TECHNOLOGY & ENGINEERING -- Material Science; Thermoplastics -- Chemical resistance